Perceived Effects and Prevention of Polycystic Ovary Syndrome among Women Living in Ilorin-South LGA, Kwara State, Nigeria - Abdulqudus Tosin Jamiu; Kamalud-deen Adekunle Uthman; Tawakalitu Kikelomo Ijaodola; Khadijah Morenikeji Mutairu; Opeyemi Funke Obaditan (Pan-African Journal of Health and Environmental Science)
Background: Women of reproductive age are susceptible to polycystic ovarian syndrome (PCOS), one of the most prevalent hormonal disorders. The disease begins at puberty and symptoms could fluctuate over time. This condition is characterized by disruption of follicular development, which affects the ovaries and ovulation. This study aimed to identify obesity and infertility as perceived effects, while checking a healthy diet as perceived prevention of polycystic ovary syndrome among women living in the study area.